NON-PENAL POLICY IN PROSECUTION TERMINATION (RECONSTRUCTING CRIMINAL LAW THROUGH RESTORATIVE JUSTICE) - Marasabessy , Fauzy; Sugiri, Bambang; Ratnohadi, Heru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
The idea of non-penal policies prioritizing rehabilitation and social reintegration rather than mere incarceration is a more humane approach in sentencing systems. However, in practice, Indonesia's criminal justice system is still dominated by retributive paradigms emphasizing vengeance. This research examines the application of restorative justice as the basis for the prosecution termination by public prosecutors. It finds that although internal regulations exist within law enforcement institutions such as the police and prosecutor's office, restorative justice implementation remains suboptimal due to structural and cultural barriers. Using a normative juridical approach, this study concludes that non-penal policies can provide solutions to prison overcapacity, enhance victim protection, and strengthen the integrated criminal justice system.